2006
DOI: 10.1080/02640410500127736
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between cohesion, collective efficacy and performance in professional basketball teams: An examination of mediating effects

Abstract: The main aim of this study was to examine mediating effects in the relationships between cohesion, collective efficacy and performance in professional basketball teams. A secondary aim was to examine the correlates of collective efficacy in a professional sport. A total of 154 French and foreign professional players completed French or English versions of questionnaires about cohesion and collective efficacy. Two composite measures of individual performance were used (pre- and post-performance). Individual-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
103
0
15

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 26 publications
13
103
0
15
Order By: Relevance
“…These actions are mostly performed by guards (Sampaio, Janeira, Ibanez, & Lorenzo, 2006;Taxildaris et al, 2001). Therefore, it is suggested that the best teams have players in this specific position better prepared to execute these tasks, building in practices and promoting in competition a stronger within-team offensive communication (Heuze, Rainbault, & Fontayne, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These actions are mostly performed by guards (Sampaio, Janeira, Ibanez, & Lorenzo, 2006;Taxildaris et al, 2001). Therefore, it is suggested that the best teams have players in this specific position better prepared to execute these tasks, building in practices and promoting in competition a stronger within-team offensive communication (Heuze, Rainbault, & Fontayne, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, to capture the basically performance is still much controversial. Some people pick the number of wins (Watson et al, 2001), some people select the original formula (Heuze et al, 2006a;Bray and Whatley, 2001), and the others choose the value of notational game analysis (Maclean and Sullivan, 2003) as performance indices. In this way, if the concept of performance deˆned is ambiguous, not only we cannot verify the relation between performance and collective e‹ca-cy, but a new problem appears.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Heuze et al (2006a) reported a complementary relationship between CE and group cohesion. Among the four dimensions of cohesion in Group Environment Questionnaire (GEQ: Carron et al, 1985;(a) Individual Attractions to the Group-Task, ATG-T; (b) Individual Attractions to the GroupSocial, ATG-S; (c) Group Integration-Task, GI-T; and (d) Group Integration-Social, GI-S), it has been reported that individual performance contributes to perceptions of CE, which in turn contribute to perceptions of GI-T.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sport researchers interested in the quality of the sport experience have implemented a variety of strategies to address their concerns. Descriptive-analytic research focusing on the behavioral assessment and analysis of behaviors in athlete-athlete interaction settings is typified by the studies of Heuzé et al (2006). Moreover, the interaction analysis strategy is to observe, describe, and analyze the quantity and quality of the interactions occurring in the sport environment for a specific period of time in game (Patterson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%